Kerja Sama Vietnam dan Tiongkok dalam Menanggulangi Armed Robbery - Devi, Lusiana; Windiani, Reni; Putranti, Ika Riswanti (Journal of International Relations, 2018)
International trade relations between Vietnam and China in the contemporary era haveshown significant progress. The increase in trading supported by geographical proximityand differences in comparative advantage of both countries. In conducting internationaltrading activities, Vietnam and China have encountered obstacle in the form of armedrobbery. This study aims to explain how Vietnam and China cooperation in tackling armedrobbery in the waters of Vietnam. This research was done by using qualitative researchmethod with descriptive research type. This research was analyzed by usinginterdependence liberalism theory, international cooperation theory and comparativeadvantage theory. The result of this research is Vietnam and China have agreed to domaritime cooperation. The cooperation is joint patrol between Vietnam and China. In theimplementation of joint patrols have demonstrated a sense of compliance between twocountries against international law. Vietnam and China's maritime cooperation aims tomaintain a cooperative relationship between countries as well as maintain the stability ofsecurity and order at sea from non-traditional threats.